Signifikansi Theologia Sistematika dalam Pemuridan bagi Pendewasaan Spiritual Jemaat - Fedlin Kukut (STAK Reformed Remnant Internasional, 2025)
This study aims to clarify and emphasize that systematic theology in discipleship is not something separate but a firm foundation in the effort to spiritually mature the congregation. This is because there is a thought that is later conveyed in church pulpits that discipleship is not a matter of theology. Discipleship is only limited to teaching the values of biblical truth without the need for theology. This view is very wrong and can result in a deviation from the real truth of the Bible. It is because of this that the researcher was stimulated to make this research so that the erroneous and distorted thinking that is currently prevalent in churches that conduct discipleship can be straightened out. This research uses a qualitative research approach with a literature study. The results of this study emphasize that systematic theology can strengthen the faith of the congregation through discipleship and provide an understanding that systematic theology is not just a science but is able to address the spiritual congregation that is discipled to become mature.